Chemical health risk assessment (CHRA) at water treatment service provider for semiconductor industry / Maisarah Yusoff - Maisarah, Yusoff (2022)
The assessment of chemical health risk in the workplace is necessary for every employer to ensure their employee's wellness under the Occupational Safety and Health Act 1994 and the Use and Standard of Exposure of Chemicals Hazardous to Health (USECHH), 2000 Regulations. In this assessment, the goal is to determine and analyse the level of chemical exposure to the workers. One work unit, which is the Facilities Workers, has been selected. The assessment was carried out according to CHRA Manual 3rd Edition. A qualitative approach was used to assess the risk and adequacy of control measures, which included a site visit, observation of employee tasks while handling chemicals, and examination of the work manual and other relevant record and documents. A total of 12 chemicals were assessed. It was concluded that all chemicals were classified as Chemicals Hazardous to Health (CHTH) but Action Priority 3 (AP3) was given, where the existing control measures were adequate to curb the exposure.